DETERMINING FACTORS OF CARDLESS CASH WITHDRAWALS USAGE AT ISLAMIC BANKS IN ACEH - Muharama, Zahara; Sanusi, Soliha; Mulia, Rika (Journal of Sharia Economics, 2026)
Digital transformation in Islamic banking has driven the development of cardless cash withdrawal services as an effort to enhance transaction convenience and flexibility for customers. However, the decision to use this service is influenced by various perceptual factors. This study aims to analyze the effects of efficiency, convenience, risk, and trust on customers’ decisions to use cardless cash withdrawal services at Bank Syariah Indonesia and Bank Aceh Syariah in Aceh. This research employs a quantitative approach using a survey method involving 100 respondents who are active mobile banking users. The data were analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that, partially, convenience and trust have a positive and significant effect on the decision to use cardless cash withdrawal services, while efficiency and risk do not have a significant effect. Simultaneously, all variables have a significant effect on usage decisions. These findings suggest that customers’ decisions are primarily influenced by service convenience and the level of trust in the security and reliability of digital Islamic banking services.